2012
DOI: 10.1007/s00210-012-0814-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mirabegron, a novel β3-adrenoceptor agonist, on bladder function during storage phase in rats

Abstract: Mirabegron, a selective β(3)-adrenoceptor agonist, facilitates urine storage function by exerting a relaxing effect on bladder smooth muscle. Here, we investigated the effect of mirabegron on bladder function during the storage phase. We assessed the effect of mirabegron on the resting intravesical pressure in anesthetized rats and also tested antimuscarinics (oxybutynin and tolterodine) under the same experimental conditions. Mirabegron dose-dependently decreased the resting intravesical pressure, while oxybu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…Whereas, the same urodynamic findings did not produce significant changes following therapy with mirabegron in line with results obtained by other authors who have shown how mirabegron can increase bladder capacity without decreasing the amplitude of the voiding contraction [15,16,17,] thus decreasing the risk of urinary retention [18]. Less capacity to induce urinary retention was found by Hatanaka et al [19] for mirabegron compared to antimuscarinics in a study performed on rats[.] As regards solifenacin, Tanaka et al [20] found a significant increase of bladder capacity and of PVR in female patients with OAB, but in this study data regarding the voiding phase of micturition have not been reported.…”
Section: Discussionsupporting
confidence: 89%
“…Whereas, the same urodynamic findings did not produce significant changes following therapy with mirabegron in line with results obtained by other authors who have shown how mirabegron can increase bladder capacity without decreasing the amplitude of the voiding contraction [15,16,17,] thus decreasing the risk of urinary retention [18]. Less capacity to induce urinary retention was found by Hatanaka et al [19] for mirabegron compared to antimuscarinics in a study performed on rats[.] As regards solifenacin, Tanaka et al [20] found a significant increase of bladder capacity and of PVR in female patients with OAB, but in this study data regarding the voiding phase of micturition have not been reported.…”
Section: Discussionsupporting
confidence: 89%
“…In rats with bladder outlet obstruction, i.v. administration of mirabegron reduced the frequency of non-voiding bladder contractions but did not affect voiding contractions, micturition pressure, threshold pressure, voided volume, residual volume, or bladder capacity (Hatanaka et al 2013a). Within that study, oxybutynin or tolterodine did not affect the frequency of non-voiding contractions, but oxybutynin significantly increased residual volume, and tolterodine reduced voided volume.…”
Section: In Vivo Animal Studiesmentioning
confidence: 73%
“…In pentobarbital-anesthetized rats, i.v. administration of mirabegron dose-dependently reduced intravesicular pressure and spontaneous bladder contractions; this was accompanied by a dose-dependent heart rate increase of up to 11 % and a mean blood pressure decrease of up to 29 % (Hatanaka et al 2013a). In rats with cerebral infarction-induced bladder dysfunction, mirabegron dosedependently increased voided volume and partly normalized it (Hatanaka et al 2013b).…”
Section: In Vivo Animal Studiesmentioning
confidence: 90%
“…Either mirabegron (0.3, 1 and 3 mg/kg), methoctramine (0.1, 0.3 and 1 mg/kg) or 4‐DAMP (0.03, 0.1 and 0.3 mg/kg) was cumulatively applied intravenously ( n = 6, each drug) at 30‐min intervals, respectively. The dosage of the drugs was selected according to previous studies . In a separate group of animals, the effects of the combined application of mirabegron (3 mg/kg) plus methoctramine (1 mg/kg) or mirabegron (3 mg/kg) plus 4‐DAMP (0.3 mg/kg) on cystometric parameters were compared with those of single‐agent application ( n = 6, each combination).…”
Section: Methodsmentioning
confidence: 99%